SILAGE PROCESS ADDITIVES - LALA, B.; PEREIRA, V. V.; POSSAMAI, A. P.S.; DINIZ, P. P.; SILVA, S. C.C; GRANDE, P. A. (Revista Brasileira de Engenharia de Biossistemas, 2010)
The aim of this review was to relate the different types of additives used for silage, its effects and ways of use. The ensiling process is aimed at proper preservation of culture for use with animals confined in periods of scarce food, and making better use of silage, the use of additives is required. Among the additives that include the promoters of the fermentation, the fermentation inhibitors, stimulators aerobic stability and nutrients. The decision about which additive to use depends mainly on the cost of use and its relation to the benefits achieved.